Flipped Classroom Learning Model, Assisted by R&D Statistics Advanced Material Module on Learning Outcomes of viewed from Mathematical Logical Intelligence - Suharianto, Joko; Thamrin, Thamrin; Andi Taufiq Umar; Mica Siar Meiriza (Department of Mathematics Education Program IPI Garut, 2024)
Penelitian ini melibatkan faktor internal berupa kecerdasan logis matematis, dan mengontrol pengetahuan awal mahasiswa. Penelitian ini membandingkan hasil belajar mata kuliah statistik inferensial yang menggunakan flipped classroom dengan direct instraction ditinjau dari kecerdasan logis matematis dengan mengontrol pengetahuan awal. Subjek penelitian terdiri dari dua kelas prodi Pendidikan Ekonomi Unimed semester ganjil 2023/2024. Jenis penelitian adalah quasi eksperimen dengan desain posttest only group control. Pengumpulan data menggunakan soal tes berupa pilihan berganda. Teknik analisis data menggunakan analisis kovarians. Hasil penelitian menunjukan terdapat perbedaan hasil belajar mahasiswa yang signifikan, model flipped classroom dibandikan metode direct instruction, setelah mengontrol pengetahuan awal; terdapat perbedaan hasil belajar yang signifikan mahasiswa dengan kecerdasan logis matematis tinggi dibanding yang rendah, setelah mengontrol pengetahuan awal; Model flipped classroom lebih efektif dalam meningkatkan hasil belajar, terutama bagi mahasiswa dengan kecerdasan logis-matematis rendah; kedua model pembelajaran dapat memberikan hasil yang baik bagi mahasiswa dengan kecerdasan logis-matematis tinggi. This research involves internal factors in the form of mathematical logical intelligence, and controlling students' initial knowledge. This research compares the learning outcomes of an inferential statistics course that uses a flipped classroom with direct attraction in terms of mathematical logical intelligence by controlling prior knowledge. The research subjects comprised two Unimed Economic Education study program classes for the odd semester of 2023/2024. This type of research is quasi-experimental with a posttest-only control group design. Data collection uses test questions in the form of multiple choices. The data analysis technique uses covariance analysis. The research results show that there are significant differences in student learning outcomes, in the flipped classroom model compared to the direct instruction method, after controlling for prior knowledge; there is a significant difference in learning outcomes for students with high mathematical logical intelligence compared to those with low, after controlling for prior knowledge; The flipped classroom model is more effective in improving learning outcomes, especially for students with low logical-mathematical intelligence; Both learning models can provide good results for students with high logical-mathematical intelligence.